Availability and maintenance scheduling of a repairable block-board manufacturing system. (2nd December 2009) - Garg, Savita; Singh, Jai; Singh, D.V.
The main objective of this paper is to develop a reliability model of a block-board manufacturing system in the plywood industry. The system discussed here undergoes partial as well as direct total failure. The model discussed here helps in calculating both time dependent and steady state availability under idealised as well as faulty Preventive Maintenance (PM). The PM rates and corrective repair rates are taken as arbitrarily distributed. Corrective repair of units is performed on the basis of preemptive resume priority discipline. The supplementary variable method is used to develop generalised expressions of state probabilities and system availabilities. Runge-Kutta method is used to calculate the availability of the system for transient state. Long run availability is carried out making use of software package Matlab 5.1. The tables for various parameters are given which are useful to the management for improving and planning the maintenance schedule.